Co-Application of Allicin and Chitosan Increases Resistance of Rosa roxburghii against Powdery Mildew and Enhances Its Yield and Quality - Jiaohong Li; Rongyu Li; Cheng Zhang; Zhenxiang Guo; Xiaomao Wu; Huaming An (MDPI AG, 2021)
Powdery mildew, caused by Sphaerotheca sp., annually causes severe losses in yield and quality in Rosa roxburghii production areas of southwest China. In this study, the role of the co-application of allicin and chitosan in the resistance of R. roxburghii against powdery mildew and its effects on growth, yield and quality of R. roxburghii were investigated. The laboratory toxicity test results show that allicin exhibited a superior antifungal activity against Sphaerotheca sp. with EC50 value of 148.65 mg kg−1. In the field, the foliar application of allicin could effectively enhance chitosan against powdery mildew with control efficacy of 85.97% by spraying 5% allicin microemulsion (ME) 100-time liquid + chitosan 100-time liquid, which was significantly (p < 0.01) higher than 76.70% of allicin, 70.93% of chitosan and 60.23% of polyoxin. The co-application of allicin and chitosan effectively enhanced the photosynthetic rate and chlorophyll of R. roxburghii compared with allicin, chitosan or polyoxin alone. Moreover, allicin used together with chitosan was more effective than allicin or chitosan alone in enhancing R. roxburghii plant growth and fruit yield as well as improving R. roxburghii fruit quality. This work highlights that the co-application of allicin and chitosan can be used as a green, cost-effective and environmentally friendly alternative strategy to conventional antibiotics for controlling powdery mildew of R. roxburghii.